(untitled) (Agricultural Engineering, 2016)
The aim of this study was to evaluate changes in the sensory properties of the table potato in relation to the use of natural sprout inhibitors during long-term storage. The material for the study consisted in four varieties of potato of the medium early group. The research was carried out in the Plant Breeding and Acclimatization Institute – National Research Institute Branch in Jadwisin in 2014-2015. After harvest potatoes were stored from the end of October to April at 5°C, at the relative humidity of 90-95%, without application of natural sprout inhibitors (control) and using the natural sprout inhibitors (essential oils). After storage, the potatoes were boiled and sensory evaluation was carried out, which includes qualities such as: over-cooking of the surface, texture, mealiness, flesh texture, taste and smell. Study results showed that long-term storage of potatoes treated with natural sprout inhibitors – peppermint, caraway and clove essential oils is significant for the changes in overcooking the surface, structure of potatoes and mealiness of tubers after cooking. The taste and smell of potato tubers depended only on the variety